Herbicide gels for controlling old mans beard (Clematis vitalba) in ecologically sensitive areas - Ward, B.G.; Henzell, R.F. (New Zealand Plant Protection, 2000)
Old mans beard (Clematis vitalba) is a significant environmental weed and can completely smother the growth of native vegetation in many New Zealand parks and reserves Current herbicide application techniques are either not effective on the weed or can have nontarget effects on adjacent native plant species HortResearch has developed herbicidal gels for the direct application to cut stems to selectively kill target plants The gels were formulated with a range of active ingredients Piclorambased gels were the most effective treatments on old mans beard without causing any non target effects